Semaphorin 3A Contributes to Secondary Blood–Brain Barrier Damage After Traumatic Brain Injury - Yang, Mengchen; Wang, Xiaoxue; Fan, Yueshan; Chen, Yaqing; Sun, Dongdong; Xu, Xin; Wang, Jianhao; Gu, Gang; Peng, Ruilong; Shen, Tianyu; Liu, Xilei; Li, Fanjian; et al. (Frontiers in Cellular Neuroscience, 2019)
Semaphorin 3A (SEMA3A) is a member of the Semaphorins family, a class of membrane-associated protein that participates in the construction of nerve networks. SEMA3A has been reported to affect vascular permeability previously, but its influence in traumatic brain injury (TBI) is still unknown. To investigate the effects of SEMA3A, we used a mouse TBI model with a controlled cortical impact (CCI) device and a BBB injury model in vitro with oxygen-glucose deprivation (OGD). We tested post-TBI changes in SEMA3A, and its related receptors (Nrp-1 and plexin-A1) expression and distribution through western blotting and double-immunofluorescence staining, respectively. Neurological outcomes were evaluated by modified neurological severity scores (mNSSs) and beam-walking test. We examined BBB damage through Evans Blue dye extravasation, brain water content, and western blotting for VE-cadherin and p-VE-cadherin in vivo, and we examined the endothelial cell barrier through hopping probe ion conductance microscopy (HPICM), transwell leakage, and western blotting for VE-cadherin and p-VE-cadherin in vitro. Changes in miR-30b-5p were assessed by RT-PCR. Finally, the neuroprotective function of miR-30b-5p is measured by brain water content, mNSSs and beam-walking test. SEMA3A expression varied following TBI and peaked on the 3rd day which expressed approximate 4fold increase compared with sham group, with the protein concentrated at the lesion boundary. SEMA3A contributed to neurological function deficits and secondary BBB damage in vivo. Our results demonstrated that SEMA3A level following OGD injury almost doubled than control group, and the negative effects of OGD injury can be improved by blocking SEMA3A expression. Furthermore, the expression of miR-30b-5p decreased approximate 40% at the 3rd day and 60% at the 7th day post-CCI. OGD injury also exhibited an effect to approximately decrease 50% of miR-30b-5p expression. Additionally, the expression of SEMA3A post-TBI is regulated by miR-30b-5p, and miR-30b-5p could improve neurological outcomes post-TBI efficiently. Our results demonstrate that SEMA3A is a significant factor in secondary BBB damage after TBI and can be abolished by miR-30b-5p, which represents a potential therapeutic target.can be abolished by miR-30b-5p, which represents a potential therapeutic target.